Structural Analysis of Treatment Cycles Representing Transitions between Nursing Organizational Units Inferred from Diabetes - Dehmer, Matthias; Kurt, Zeyneb; Emmert-Streib, Frank; Them, Christa; Schulc, Eva; Hofer, Sabine (PUBLIC LIBRARY SCIENCE, 2015)
In this paper, we investigate treatment cycles inferred from diabetes data by means of graph theory. We define the term treatment cycles graph-theoretically and perform a descriptive as well as quantitative analysis thereof. Also, we interpret our findings in terms of nursing and clinical management.
Keywords: NETWORK ANALYSIS; Science & Technology - Other Topics